A shadow Markov equation - Bonin, Nathan; Ovsienko, Valentin (Comptes Rendus. Mathématique)
We introduce an analogue of the classical Markov equation that involves dual numbers $a+α ε $ with $ε ^2=0$. This equation characterizes the “shadow Markov numbers” recently considered by one of us. We show that this equation is characterized by invariance by cluster algebra mutations.